Digital entrepreneurship as a strategic socioeconomical enhancement method for communities - Mohamad, Zaleha; Ahmad Khairuddin, Muhammad Afiq; Lani, Mohd Nizam; Zainuddin, Nur Munirah; Ismail, Ahmad Fadzil; Ngah, Rohana; Che Abdullah, Azmah (Allied Business Academies, 2020)
Digital entrepreneurship has gotten its eyes around the globe with catalyst that consists of private and public relationships and global free market, the Digital Free Trade Zone (DFTZ) sets its base on Malaysia. Prior to this unique opportunity, this paper explains about the socioeconomic enhancement of the community in Kg. Telaga Papan, Setiu in the state of Terengganu with a test pilot questionnaire. From the data it is concluded by the linear regression model of the factors that taken account for, that the community shows particular interest of the strategic new market driven by digital entrepreneurs. © 2020, Allied Business Academies.